The brain mechanisms of Bafa Wubu of Tai Chi exercise enhancement on inhibition of college students - Shen, Qiqi; Yin, Hengchan; Cui, Lei (The Journal of the International Society of Chinese Health Practices, 2021)
Objective: Inhibition refers to the ability to inhibit dominant, automated, or dominant responses, including the use of attentional control to resist interference from stimuli or responses unrelated to the task. As core of executive function, it was an important component of individual cognitive and social functions. inhibition is an important component of learning, reasoning, problem solving and other intellectual activities and crucial to the healthy development of an individual’s mind, body and brain. Studies found that inhibition could be changed throughout the life cycle. Therefore, exploring effective ways to improve inhibition has become a focus of researchers in multiple disciplines. Contemporary college students are not only important national talents that are cultivated, but also senior personnel, builders and successors of the country’s future. inhibition is very important for college students’ social achievement and quality of life. Recent studies in the field of psychology have shown that cognitive training mindfulness training can effectively improve the inhibition of college students. Studies in the field of exercise psychology have found that exercise can improve inhibition, but few of them involve college students. Tai chi Chuan (TCC), which belongs to mindful exercise, is a health and fitness exercise with distinct Chinese traditional cultural characteristics. Recently, to accelerate the implementation of the Healthy China, the General Administration of Sport of China (GASC) has launched the new routine-Bafa Wubu of Tai Chi (BWTC) in order to better promote and popularize TCC and solve the practical problems such as high threshold and complex structure of the previous TCC routine. Our previous studies found that acute BWTC exercise could improves college students’ inhibion, Therefore, to explore whether long term BWTC intervention can improve the inhibition of college students, and whether the effect is better than other sports, and how its brain mechanism can provide theoretical and practical basis for the use of better exercise means to promote the development of college students’ inhibition, and provide scientific basis for the popularization of BWTC. This study used psychological measurement and functional multimodal magnetic resonance imaging (fMRI) to explore the long-term BWTC intervention on the inhibiton of college students and on brain functional plasticity. Revealing the brain mechanism of BWTC to enhancement on inhibition in college students. This study consists of two parts. Method: Thirty-six college students were grouped into TCC (Bafa Wubu of Tai Chi), general aerobic exercise (brisk walking) and control groups. Analyzed and compared the changes of EF before and after eight weeks exercise intervention. We can conclude that BWTC can improve the processing efficiency of inhibtion and the effect is better than brisk walking. Individuals were assessed with a rs-fMRI scan before and after an eight weeks training period. Results: We can conclude that compared with general aerobic exercise, eight weeks of BWTC exercise has a stronger effect on brain plasticity, which is embodied in the increase of the fALFF of right fusiform gyrus and right medial superior frontal gyrus, and decreased fALFF of left dorsolateral superior frontal gyrus and right central parietal lobule. Compared with general aerobic exercise, BWTC significantly increased the fALFF of right medial superior frontal gyrus. There was a significant negative correlation between the response time (RT) change of inhibiton and the change of fALFF in the left medial superior frontal gyrus. The enhancement of fALFF in the left medial superior frontal gyrus could significantly predict the decrease in RT of inhibiton function. Conclusion: the results showed that: (1) Long-term BWTC can improve the inhibiton of college students, and the effect is better than brisk walking. (2) Long-term BWTC can effectively promote the brain function. (3) BWTC has advantages in improving the inhibition of college students, And the brain mechanism may promote the optimization of spontaneous neural activity in the brain.